Adesão medicamentosa e fatores associados em idosos de um ambulatório filantrópico do Espírito Santo - Arruda, Daiane Campos Juvêncio de (2013)
The incorrect use of medications, underuse, the irrational use or not use the total prescribed medication, are forms of non-adherence to medication. The prevalence ranges from 40 to 60% in the general population and can not be seen as an isolated phenomenon. Should evaluate the individual characteristics, the sociodemographic, health conditions and the use of drugs of the subject. The lifestyle and sociodemographic conditions may be associated with medication nonadherence due regard to the health of the individual. The aim of this study was to estimate the prevalence and factors associated with medication non-adherence in the elderly. Descriptive study, analytical, through interviews using a script prepared, organized and divided into blocks according to sociodemographic variables, health status, lifestyle and medications taken. To verify the non pharmacological treatment we used the instrument Adherence Measure Therapeutics. The sample consisted of 270 individuals aged 60 years or older with cardiovascular disease and who underwent outpatient treatment at the Hospital Santa Casa de Misericordia de Vitoria. Descriptive statistics, tests of association by chisquare, prevalence ratios and 95% confidence. Multivariate analysis was performed for multiple Poisson regression. Of the 263 respondents selected for the study, 26.7% reported not adhering to drug treatment. The findings of this research indicate that the lack of employment of the occupation earlier, the presence of cognitive decline and poor diet are associated with medication non-adherence in this population. Thus, the mental state, behavior of healthy living and better socioeconomic conditions may be factors in medication adherence in elderly outpatients.